Navigating the Black Box: Transparency Requirements for Medical AI - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming diagnostics and treatment. As AI systems take on critical roles in clin...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care